Sistem Penilaian Proposal Penelitian Dosen Universitas Muhammadiyah Purwokerto Berbasis Web Service dengan Android - Hananto Adi Nugroho; Tito Pinandita (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2013)
Web Service is an application that is made to be invoked or accessed by other applications via the Internet or intranet by using XML as a messaging format. The reason for the use of the concept of Web services is to create an application that can be accessed through a variety of platforms, programming languages, and operating systems. One platform can implement the Web Service is the Android Operating System Application. Android is an operating system that uses the Linux kernel being owned by Google. The technology allows the computation process can be integrated with a variety of daily activities to reach people who are not confined in one area or an area scope. Application Assessment Proposal is the result of appraisal value proposer faculty research proposals from each of the assessment criteria. Value will be accessible through Android SmartPhone applications that have been installed. The advantages of smartphones is much easier and efficient in accessing